Age of Infection with Kaposi Sarcoma–Associated Herpesvirus and Subsequent Antibody Values Among Children in Uganda. Issue 8 (August 2018) - Nalwoga, Angela; Miley, Wendell; Labo, Nazzarena; Elliott, Alison; Cose, Stephen; Whitby, Denise; Newton, Robert
Abstract : We investigated associations between Kaposi sarcoma–associated herpesvirus (KSHV) seroconversion age and KSHV antibody values in Ugandan children. Every annual delay in KSHV seroconversion age was associated with a reduction of 19% ( P < 0.0001) in K8.1 and 27% ( P < 0.0001) in ORF73 antibody values at 6 years of age. Early infection may be an important risk factor for KSHV pathogenesis and viral shedding in saliva, leading to transmission. Abstract : Supplemental Digital Content is available in the text.